In vitro oxidative potential (OP) assessment for indoor airborne particulate matters (PM) at selected primary schools in Pahang - Maryam binti Zahaba (Kulliyyah of Science, International Islamic University Malaysia, 2019)
The inadequacy of Indoor Air Quality (IAQ) inside the classrooms especially in tropical countries has been highlighted in previous research, and the increased respiratory symptoms among the schoolchildren were associated with this inadequacy of IAQ issue. Therefore, this study aimed to assess the selected IAQ parameters (temperature, relative humidity (RH), air movement and particulate matter (PM)) at different backgrounds of sampling locations (industrial, residential and rural areas) and monsoonal variations during occupied and non-occupied periods. The next objective was to determine the prevalence of respiratory symptoms among the schoolchildren and its association with IAQ parameters. The last objective was to assess the PM-induced oxidative activity by using an in vitro synthetic respiratory tract lining fluid (synRTLF) model. Initially, the IAQ monitoring was conducted at the selected primary school buildings in different background areas (industrial, residential and rural). This study was conducted twice during the southwest monsoon (from May to October 2015) and the northeast monsoon (from November 2015 to April 2016). Then, the association between respiratory symptoms and indoor PM mass concentration was determined using a chi-squared test. Prior to that, the prevalence of chronic respiratory symptoms; non-specific respiratory disease (NSRD) and persistent cough and phlegm (PCP) was assessed using questionnaires adapted from a well-established questionnaires (ATS-DLD-78-C). A further assessment of indoor PM toxicity or oxidative activity was conducted using a novel method, namely synRTLF in order to obtain the PM OP metrics. From the IAQ assessment, thermal comfort parameters (temperature, RH and air movement) were influenced by the Malaysian hot and humid climate. A two-way ANOVA analysis showed that thermal comfort parameters were significantly different between two monsoons (p < 0.05). Based on the two-way ANOVA analysis, there was a significant effect of monsoonal variations on the TSP, PM10, PM2.5 and PM1 concentration. During SW season, the TSP PM10, PM2.5, and PM1 concentrations were significantly higher than NE season (p < 0.001). Meanwhile, the prevalence of NSRD and PCP was low. For SW monsoon, the highest prevalence of persistent phlegm (15.7%), wheezing (12.0%), and chronic bronchitis (3.9%) was recorded in SKIM, while the highest prevalence of persistent cough (15.0%) and bronchial asthma (12.2%) was recorded in SKT. In comparison with NE monsoon, the highest percentages of bronchial asthma (9.8%) and persistent phlegm (1.2%) were recorded in SKT, persistent cough (4.8%) in SKIM, while wheezing (1.9%) and chronic bronchitis (0.7%) in SKBB. Bronchial asthma and persistent cough were the most common symptoms significantly associated with coarse PM mass concentration. Furthermore, from the independent t-test analysis, there was no significant difference for indoor and outdoor PM OP metrics (p > 0.05). A higher PM OP metrics was recorded at the schools located nearer to the main roads. In conclusion, the inadequacy of IAQ status at the classrooms was mainly influenced by monsoonal varieties and outdoor ambient background location. A low prevalence of respiratory symptoms was recorded, and from the PM OP metrics result, PM toxicity was observed especially in PM collected at the schools' proximity to main roads.